Health behavior theory, research, and practice - Glanz, Karen; Rimer, Barbara K.; Viswanath, K. (Kasisomayajula) (San Francisco, CA Jossey-Bass, 2015)
"Health Behavior: Theory, Research, and Practice, Fifth Edition, is a thorough introduction to the practice of health education and health promotion, covering the theories, applications, and research of most use to public health students and practitioners. Through four editions, with more than 100,000 copies sold, this book has become the gold-standard textbook for health behavior courses. This essential resource includes the most current information on theory, research, and practice at individual, interpersonal, and community and group levels, with substantial new content on current and emerging theories of health communication, social marketing and e-health, culturally diverse communities, health promotion, the impact of stress, the importance of networks and community, social marketing, and evaluation. New contents include an update to the selection of theories, both established and emerging; e-health and social media as integrated into health communication; global health as an application of health behavior theory; culture and health disparities; more guidance on how to select suitable theories for specific problems/issues. In addition to a selection of basic ancillary materials, the editors offer a dedicated website with student-written "theory in action" examples; expanded bibliographies; exemplar measures of theoretical constructs; and relevant links"-- Provided by publisher.
The scope of health behavior The Editors -- Theory, research, and practice in health behavior The Editors -- Ecological models of health behavior James F. Sallis and Neville Owen -- Introduction to health behavior theories that focus on individuals Barbara K. Rimer and Noel T. Brewer -- The health belief model Celette Sugg Skinner, Jasmin Tiro, and Victoria L. Champion -- heory of reasoned action, theory of planned behavior, and the integrated behavioral model Daniel E. Montaño and Danuta Kasprzyk -- The transtheoretical model and stages of change James O. Prochaska, Colleen A. Redding, and Kerry E. Evers -- Introduction to models of interpersonal influences on health behavior Catherine A. Heaney and K. Viswanath -- How individuals, environments, and health behaviors interact Steven H. Kelder, Deanna Hoelscher, and Cheryl L. Perry -- Social support and health Julianne Holt-Lunstad and Bert N. Uchino -- Social networks and health behavior Thomas W. Valente -- Stress, coping, and health behavior Elaine Wethington, Karen Glanz, and Marc D. Schwartz -- Interpersonal communication in health and illness Ashley Duggan and Richard L. Street Jr. -- Introduction to community and group models of health behavior change Karen Glanz and Alice Ammerman -- Improving health through community engagement, community organization, and community building Nina Wallerstein, Meredith Minkler, Lori Carter-Edwards, Magdalena Avila, and Victoria Sanchez - Implementation, dissemination, and diffusion of public health interventions Ross C. Brownson, Rachel G. Tabak, Katherine A. Stamatakis, and Karen Glanz -- Communication and health behavior in a changing media environment K. Viswanath, John R. Finnegan Jr., and Sarah Gollust -- Introduction to using theory in research and practice The Editors -- Planning models for theory-based health promotion interventions L Kay Bartholomew, Christine Markham, Pat Mullen, and Maria E. Fernandez -- Behavioral economics and health Kevin Volpp, George Loewenstein, and David Asch -- Social marketing J. Douglas Storey, Ronald Hess, and Gary Saffitz.
Revision of: Health behavior and health education. 2008. 4th ed.
Includes bibliographical references and indexes.
Keywords: Health behavior; Health education; Health promotion